Proposal of STBC MIMO-OFDM for ITS systems - Mata, Tanairat; Naito, Katsuhiro; Boonsrimuang, Pisit; Mori, Kazuo; Kobayashi, Hideo (My University, 2013)
Orthogonal Frequency Division Multiplexing (OFDM) is a popular technique in the wireless communication systems which can achieve high transmission data rate with high signal quality even in the multipath fading channel which is a typical operation condition under wireless communication systems. MIMO (Multi Input-Multi Output)-OFDM is also considered as a promising technique for realizing the future ITS services. In this paper, we propose a new road to vehicle communication system (RVC) for the ITS by using the STBC MIMO-OFDM technique which can achieve a high transmission data rate with high signal quality even under the high mobile ITS environments. © 2013 IEEE.
Keywords: ITS; MIMO; OFDM; RVC; STBC